Impact of Exercise Stress Testing on Diagnostic Gene Expression in Patients With Obstructive and Nonobstructive Coronary Artery Disease - Filsoof, David M.; Safford, Robert E.; Newby, Kristin; Rosenberg, Steven; Kontras, Dana G.; Baker, Alice; Odunukan, Olufunso W.; Fletcher, Gerald (The American journal of cardiology, 2015)
A blood-based gene expression test can diagnose obstructive coronary artery disease (CAD). The test is sensitive to inflammatory and immune processes associated with atherosclerosis. Acute exercise engages short-term inflammatory pathways, and exercise stress testing may affect results of gene expression testing during the same diagnostic workup. The objective of this study was to evaluate the effect of exercise on diagnostic gene expression testing. Ten patients with obstructive CAD (≥50% stenosis) and 10 with no/minimal CAD (≤20% stenosis) were identified by angiography. Blood samples for gene expression were obtained at baseline, peak exercise, 30 to 60 minutes after testing, and 24 to 36 hours after testing. Core-lab gene expression analysis yielded raw gene expression scores (GES) for each time point. Linear models were used to estimate changes in GES, adjusting for CAD status and other covariates. GES increased during peak exercise across both genders, with no significant differences as a function of CAD status. The overall adjusted mean GES increase at peak exercise was 0.29 (95% confidence interval 0.22 to 0.36; p <0.001). GES after exercise were not significantly different from baseline. The change in gene expression levels during peak exercise may reflect a transient inflammatory response to acute exercise that may be independent of patient gender or CAD status. In conclusion, CAD GES increase at peak exercise testing and rapidly return to baseline. Such may reflect a transient inflammatory response to acute exercise independent of gender or extent of CAD.